Re-locating the Self: Portraiture for Teacher Professional Growth (LEARNing Landscapes, 2016)
In this article, three teachers at various career-stages describe the process and share evidence of artful exploration and engagement through self-portraiture (Lawrence- Lightfoot & Ho mann Davis, 1997). The development of performance, poetic, and visual renderings of self proves empowering and transformative. Insights are gained through public presentation of portraits and involvement with colleagues as they create their own portrayals. Using literary métissage (Hasebe-Ludt, Chambers, & Leggo, 2009) to braid voices across locations, emergent issues of vulnerability, community, and the possible contribution of teacher inquiry to knowledge of teachers, teaching, and learning are discussed.
Keywords: self-portraiture; artful inquiry; transformation; literary métissage; teaher inquiry